Books & coffee trolley round - Amno, Hasniza; Shaharuddin, Bakiah; Mansor, Mohamed Hafiz; Azmi, Muhamad Amin (Universiti Teknologi MARA, Kedah, 2019)
The "Books and Coffee Trolley Round" is a weekly programme conducted at the Clinical Complex of Advanced Medical and Dental Institute (AMDI). AMDI provides clinical expertise in various disciplines, while oncology services (cancer treatment) is our thrust area. This programme is jointly organised by the Clinical Division and AMDI Library. This programme was launched on 26th April 2019 and runs every Friday morning. It takes off from the "Jom! Derma Buku" campaign and the "Free Books Corner" service that was launched at the initial stage. Through this programme, AMDI Library collaborates with multiple parties and external organisations such as charity foundations, book publishers, suppliers, and volunteers from NGO or private individuals. This programme also intends to increase the passion for physical reading materials which still have a role to provide valuable knowledge and skills to the community; especially to children who are constantly exposed to electronic devices. In addition, we managed to form a networking environment with the industry and community; the community that we engage are mostly cancer patients who are at various stages of diagnosis, treatment and outcomes. Our patients and their family members value the weekly visits from our volunteers who are medical specialists, university lecturers, cancer survivors, administrative staff and others, who commonly dispense with support and motivation. This effort demonstrates a caring and empathic society. Results from a feedback survey among 100 respondents demonstrated that 63% are “very satisfied” and 35% “satisfied” with this programme. As for it being an added value to our clinical service, a majority of respondents (64%) are “very satisfied” with this statement. Further results will be provided during presentation at our booth. In conclusion, this programme is an innovative extension of a Library service, which is quite different from the conventional services.